2017
DOI: 10.1186/s12889-017-4023-3
|View full text |Cite
|
Sign up to set email alerts
|

Designing an optimal HIV programme for South Africa: Does the optimal package change when diminishing returns are considered?

Abstract: BackgroundSouth Africa has a large domestically funded HIV programme with highly saturated coverage levels for most prevention and treatment interventions. To further optimise its allocative efficiency, we designed a novel optimisation method and examined whether the optimal package of interventions changes when interaction and non-linear scale-up effects are incorporated into cost-effectiveness analysis.MethodsThe conventional league table method in cost-effectiveness analysis relies on the assumption of inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…These studies span from 2007 to 2017 with 42 studies modelling oral PrEP in sub‐Saharan Africa and two studies with non‐specific settings but of relevance for generalized HIV epidemics. Applications of country‐specific modelling of oral PrEP occurred predominantly for South Africa and Kenya , followed by Botswana , Zambia , and one application each for Zimbabwe , Mozambique , Nigeria , and Uganda . Select country‐specific results were additionally presented in two studies .…”
Section: Resultsmentioning
confidence: 99%
“…These studies span from 2007 to 2017 with 42 studies modelling oral PrEP in sub‐Saharan Africa and two studies with non‐specific settings but of relevance for generalized HIV epidemics. Applications of country‐specific modelling of oral PrEP occurred predominantly for South Africa and Kenya , followed by Botswana , Zambia , and one application each for Zimbabwe , Mozambique , Nigeria , and Uganda . Select country‐specific results were additionally presented in two studies .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that oral PrEP is only cost‐effective when provided to individuals at very high risk of HIV infection . Others have ranked PrEP for cost‐effectiveness along with other HIV interventions within countries . Verguet, et al examined the impact and cost‐effectiveness of PrEP for the general population across 42 sub‐Saharan African countries, finding that it was only cost‐effective for this population in countries with high HIV prevalence and low male circumcision prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Cost effectiveness was expressed as incremental cost across the entire HIV programme per life year saved over 20 years (2016–2035) [ 13 ]. We estimated the epidemiological impact in terms of life years saved relative to the West level 26 life table, a life table representing population survival at very low levels of HIV prevalence [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The optimization method has been described in detail elsewhere [ 13 ]. It used a rolling baseline that started with the most cost-effective intervention (lowest ICER) and then sequentially added interventions in order of incremental cost-effectiveness, with the baseline re-estimated after the addition of each new intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation